THE CHARACTERISTICS OF COFFEE POWDER QUALITY IN TREATMENT FERMENTATION TIME AND TEMPERATURE IN MEDIUM KOMBUCHA TEA - Aprilia Pratiwi, Fitri; Suryawan Wiranatha, Anak Agung P.A.; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The purposes of this study were: 1) to determine the effect of fermentation’s time and temperature of coffee in the medium of kombucha tea on the characterictics of coffee’s quality, and 2) to determine the appropriate fermentation’s time and temperature of coffee in the medium of kombucha tea to produce the best quality coffee. The research was undertaken by using a Randomized Factorial Block Design experiment with two factors, namely (i) fermentation’s time (12, 24, and 36 hours), and (ii) fermentation’s temperature (22±1 o C, 26±1 o C, 30±1 o C). The research results show that the treatment of 24 hours of fermentation’s time and the fermentation’s temperature of 30±1 o C has the best result. This treatment produced the coffee with the coffee’s characteristics, as follow: 0.088% ash content; pH 5.84, organoleptic taste 5 (typical coffee), flavour 5.3 (typical coffee to very typical coffee), and overall acceptance 5,35 (mostly like to like). This treatment also produced the organic acids as follow: oxalic acid (0.086±0.000% to 0.089±0.001%), ascorbic acid (0.139±0.003% to 0.281±0.004%), lactic acid (0.193±0.062% to 0.160±0.003%), malic acid (0.539%±0.000% to 0.560±0.003%), acetic acid (0.752±0.007% to 0.789±0.006%), propionate acid (1.134±0.000% to 1.142±0.001%), and butyric acid (2.281±0.051% to 2.573±0.001%). Key Words: coffee, kombucha tea, fermentation, organic acid
Keywords: 26